Effect of granaticin on the activity of DNA-directed RNA polymerase from Streptomyces granaticolor - Smardová, J; Spízek, J; Stastná, J; Klégr, M (Folia microbiologica, 1989)
DNA-directed RNA polymerase was isolated from wild-type and mutant (asporogenic and granaticin overproducing) Streptomyces granaticolor. The effect of granaticin on the enzyme activity was compared with that of standard transcription inhibitors, rifampicin and rifamycin SV and shown to be zero.
Keywords: antibakteriální látky; DNA-Directed RNA Polymerases; Naphthoquinones; DNA řízené RNA-polymerasy; Anti-Bacterial Agents; naftochinony; Streptomyces